(untitled) (SAARC Journal of Agriculture, 2016)
The experiment was conducted to study the performance of three T. Aman varieties (BR22, BRRI dhan46 and BRRI dhan49) under normal transplanting with 30, 45 and 60 days old seedlings and double transplanting ( 30 days + 30 days) system at Plant Physiology Division of Bangladesh Rice Research Institute, Joydebpur, Gazipur during T. Aman season, 2013. Interaction effect was significant only for days to maximum flowering and sterility percentage. BR22 required longer duration to complete flowering when transplanted with 60 days old seedlings, while sterility percentage was higher in BRRIdhan 49 when transplanted with same aged seedlings. Photosynthetic rate, LAI, total dry matter production, yield contributing characters and harvest index of tested varieties were insignificant under different transplanting methods; these parameters contributed to produce similar grain yield. The results revealed that rice varieties BR22, BRRI dhan46 and BRRI dhan49 showed similar performance under normal transplanting with different aged seedlings and double transplanting in respect of photosynthetic rate, tillering pattern, LAI, total dry matter production and grain yield during T. Aman season. SAARC J. Agri., 14(1): 37-45 (2016)